فاعلية المؤشرات المالية للمصارف العراقية في الاستقرار النقدي مع التركيز على مؤشر السيولة النقدية في عينة من المصارف التجارية للمدة 1997 – 2011 (المجلة العراقية للعلوم الاقتصادية, 2018)
The financial stability is of great importance to enable the financial sector, in general, and banking sector, in particular, on the face of risk or any adverse effects on the current and future reality for the growth of the national economy and its development, hence the damage to the efforts of financial stability will result to harm economic stability, in general, and monetary stability, in particular, which represents the essence of the work of the central bank, and a key target of its goals set forth in the provisions of law No. (56) for the year 2004, the central bank has focused on continuous communication with the banking system units, and create conditions that foster a supportive banking environment for the monetary stability, as well as the duties, functions and powers of the central bank, and its full ability to intervene in the banking system institutions, through its monetary and supervisory tools